1997
DOI: 10.1002/ange.19971092316
|View full text |Cite
|
Sign up to set email alerts
|

Hochenantioselektive katalytische 1,4‐Addition und kombinierte 1,4‐Addition/Aldolreaktion von Organozinkreagentien an Enone

Abstract: ZUSCHRIFTENKristallstrukturdaten von [ ( K+)2(22-)( [18]krone-6),]: C&,H,K,OI2, P2,/n, a = 13.959(1), 6=10.403(1), ~=19.733(1)A,fi=107.376(1)', V=2740.31 A', 2 = 2 , phcr= 1.19 gcm-', p =0.22 mm-l, T = 150 K; Kristalldimension ca. 0.20 x 0.25 x 0.40 mm, 90 Rahmen, 29 555 gemessene (6266 unabhangige) Reflexe, R = 0.0422 und R, =0.0464 fur 5403 Reflexe mit I > 3 4 I ) ; m a x h i n . Restelektronendichte in der letzten Differenz-Fourier-Synthese: 0.361 -0.23 e A-3. Fur die Strukturverfeinerung wurde ein Gewichtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 28 publications
3
41
0
4
Order By: Relevance
“…On the basis of this information on the face-selectivity step, we consider that the role of effective chiral ligands reported recently [55] is to selectively accelerate reductive elimination of the CPop intermediate, most likely through complexation of the phosphorus moiety of the ligand to the Cu III atom in TScc. Note that this view is quite different from the prevailing views on enantiofacially selective conjugate addition that focus on the copper/olefin 1-complexation stage (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this information on the face-selectivity step, we consider that the role of effective chiral ligands reported recently [55] is to selectively accelerate reductive elimination of the CPop intermediate, most likely through complexation of the phosphorus moiety of the ligand to the Cu III atom in TScc. Note that this view is quite different from the prevailing views on enantiofacially selective conjugate addition that focus on the copper/olefin 1-complexation stage (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach is to apply the rhodium-catalyzed asymmetric 1,4-addition [8,9] to the asymmetric synthesis of a-aryl ketones. Herein we report that the asymmetric 1,4-addition of aryl-and alkenylboron reagents to quinone monoketals [10] is efficiently catalyzed by a chiral diene/rhodium complex [11][12][13][14] and one of the enantioenriched addition products (96-99 % ee) is readily converted into a 2-aryltetralone without loss of enantiomeric purity. …”
mentioning
confidence: 99%
“…For example, the hydrogenation of 1a was completed within 6 h in the presence of 10 mol% KI, yielding the product (R)-2a in the same ee value as that with added I 2 (entry 12 vs. 1). Ligand comparison showed that the binaphthol-based phosphoramidites (S a ,S,S)-Monophos-pe [(S a ,S,S)-4a] and (S a ,R,R)-Monophos-pe [(S a ,R,R)-4b] [25] were also suitable ligands for the reaction (80% ee and 94% ee, respectively) and the configuration of product was interestingly mainly determined by the chirality of the amino moiety of the ligand Monophos-pe (entries 21 and 22). In contrast, other monodentate phosphorus ligands (entries [15][16][17][18][19][20] and bidentate phosphine ligands such as SDP, BINAP and Josiphos (data not shown) were unsuitable for this reaction, giving very low ee values.…”
Section: Resultsmentioning
confidence: 99%